PENGARUH MOTIVASI KONSELI DAN SIKAP EMPATI KONSELOR TERHADAP KEBERHASILAN PROSES KONSELING - Mudjijanti, Fransisca (Widya Warta, 2012)
The effectiveness of problem solving through counseling can really be detected since the counselee begins to have a problem, namely when the counselee realizes that he has a problem. Counseling with people who are not aware of the problem is actually not effective. Counselee’s motivation to come to a counselor on the basis of awareness that he has a problem and is in need of someone else becomes a requirement of a successful guiding. In addition to the counselee’s motivation, another factor that influences the success of counseling  is  the  counselor’s  emphaty.  A  counselor’s  ability  to  show  emphaty   is   very important and indispensable to the success of counseling. The formulation of the problem of this study is as follows: 1. Is there a significant effect of counselee’s motivation on the success of    counseling process? 2. Is there a significant effect of counselor’s empathy on the success of    counseling process? 3. Is there a significant effect of counselee’s motivation and counselor’s empathy on the success of counseling process? The results of the correlation coefficient analysis showed that there was a great correlation between counselee’s motivation and counselor’s empathy and the success of counseling process as indicated by the correlation value 0.41-0.70 The analysis of determination coefficient showed that the success of counseling process was influenced by counselee’s motivation and counselor’s empathy by 23%. The result of t test showed that the first hypothesis, which reads "counselee’s motivation significantly influences the success of counseling process" was accepted and the second hypothesis, which reads" counselor’s emphaty significantly influences the success of counseling process" was accepted. The results of F test showed that the major hypothesis that reads "motivation counselee’s and counselor’s emphaty significantly influence the success of counseling process" was accepted.